Effectiveness of the probiotic Streptococcus salivarius K12 for the treatment and/or prevention of sore throat: a systematic review. (June 2019) - Wilcox, C.R.; Stuart, B.; Leaver, H.; Lown, M.; Willcox, M.; Moore, M.; Little, P.
Abstract: Background: Sore throat resulting from pharyngotonsillitis is one of the commonest reasons for primary care consultation and inappropriate antibiotic prescription and finding effective alternative treatments is important. Objectives: To review the evidence for using the probiotic Streptococcus salivarius K12 ( Ss K12) for the prevention or treatment of pharyngotonsillitis. Data Sources: PubMed, Embase, CINAHL and Cochrane Library. Study eligibility criteria: Randomized controlled trials (RCTs). Participants: Adults or children. Interventions: Ss K12 as active treatment or prophylaxis, against pharyngotonsillitis. Methods: Literature search. Results: Four articles were identified (1846 participants). All were deemed to be of poor quality using the Cochrane risk-of-bias assessment. Two trials studied Ss K12 prophylaxis for streptococcal pharyngitis (children without history of recurrence). One compared daily administration of Ss K12 to no treatment over 6 months ( n = 222, age 33–45 months), reporting significantly lower incidence in the Ss K12 group (16.2% vs. 48.6%, p < 0.01), whereas another placebo-controlled RCT over four school terms ( n = 1314, 5–14 years) found no significant difference (7.8% vs. 8.8%, p 0.34) with Ss K12 (administered on school days). Another trial found daily Ss K12 to significantly protect children ( n = 250, 6–7 years) against chronic adenoiditis exacerbation over 3 months compared to no treatment (71.7% vs. 100%, p < 0.0001). The one placebo-controlled RCT in adults that studied the use of Ss K12 for acute pharyngotonsillitis (concurrently with penicillin) showed no significant benefit. In all trials, Ss K12 was safe and well tolerated. Conclusions: Ss K12 appears safe and well tolerated. However, further RCTs are required to establish its role as a prophylactic therapy, particularly among patients experiencing frequent exacerbations of pharyngitis. In the acute setting, Ss K12 is unlikely to be effective if given concurrently with antibiotics; however, further RCTs should establish its role as an alternative to antibiotics in nonsevere cases or when prescribed after antibiotic therapy for the prevention of disease recurrence and/or secondary infection.